How anatomical is our tunnel? A three dimensional CT evaluation of femoral tunnel in anatomic anteromedial single bundle anterior cruciate ligament reconstruction - Dutt, Saurabh; Kumar, Vinod (International Journal of Research in Orthopaedics, 2019)
Background: ACL reconstruction has become a common orthopaedic procedure. The anatomy and biomechanics of ACL have been one of the most researched and debated topics in the orthopaedic literature. This has implication on the surgical procedure too with shift from traditional transtibial to more anatomic anteromedial ACL reconstruction. Anteromedial technique results in more anatomic femoral tunnel with graft positioned at the native insertion site. The tunnel position is crucial for better outcome after ACL reconstruction. The purpose of the study was to ascertain the femoral tunnel position made by anatomic single bundle reconstruction with the help of three dimensional computer tomography. Methods: A prospective case series involving thirty patients with ACL tear who underwent anteromedial single bundle ACL reconstruction. Computer tomography scans were performed on thirty knees that underwent single bundle anteromedial ACL reconstruction. Three dimensional models were created and the data was analyzed according to coordinate system method. Femoral tunnel position was measured in proximal to distal and posterior to anterior directions. This data was compared with the already published reference data on anatomical tunnel position. Results: Femoral tunnel centre on the medial wall of lateral femoral condyle was located at 35±9% in the posterior to anterior direction. In the proximal to distal direction, the tunnel was placed at 30±12%. Femoral tunnel was placed anteriorly as compared to anatomic anteromedial and posterolateral tunnel position. There was no significant difference in tunnel position in proximal to distal direction. Conclusions: Femoral tunnel centre on the medial wall of lateral femoral condyle was located at 35±9% in the posterior to anterior direction. In the proximal to distal direction, the tunnel was placed at 30±12%. Femoral tunnel was placed anteriorly as compared to anatomic anteromedial and posterolateral tunnel position. There was no significant difference in tunnel position in proximal to distal direction.